Determinants of accounting choice of noncurrent assets at IFRS first adoption among Nigerian firms - Isa, Muhammad Aminu (Elsevier Ltd., 2014)
This study examines the determinants of accounting choices for noncurrent assets by Nigerian firms at IFRS first adoption within the framework of positive accounting theory.Data were randomly collected from the annual reports of thirty firms that met the adoption target of 2012 and regression technique was used for the analysis.Firms’ size and ownership concentration are found as predictors of accounting choice for non-current assets.In addition, the firms mainly choose income increasing strategy by the predominant use of cost model and firms with higher ownership concentration tend to use more of fair value model than income increasing strategy.